FORMATION OF PRACTICAL CLASSES ON INFORMATION TECHNOLOGIES IN HIGHER EDUCATIONAL INSTITUTIONS (Web of Technology: Multidimensional Research Journal, 2024)
Nowadays, information technologies provides a clear and easy-to-perform practical task that helps students to form existing knowledge and skills, to use interesting schemes, diagrams, various charts and tables to help them understand it in practical assignments. special attention, etc. are often used. The article provided ample opportunities for students to master many basic concepts relatively easily, conveniently, and robustly. An important factor in this regard is the creation of methodological guidelines, methodological guidelines for the organization of practical training in higher education and their application in the educational process.